Enhancing Learning Outcomes: The Impact of Contextual Learning with E-LKPD Liveworksheets on Colligative Properties - Utami, Syiane; Feronika, Tonih; Wardani, Miessya (LAVOISIER: Chemistry Education Journal, 2024)
This study aims to determine the effect of the contextual learning model assisted by E-LKPD Liveworksheets on student learning outcomes on the material of colligative properties of solutions. This research was conducted in one of the public high schools in South Tangerang using the quasi-experiment method and non-equivalent control group design. Sampling using a purposive sampling technique consisting of 40 students of class XII MIPA 2 (control class) and 40 students of class XII MIPA 3 (experimental class). Data collection using a multiple choice test of 30 questions. The results of hypothesis testing of learning outcomes data using the t-test (Paired Sample Test) with a significance level of 5% obtained an Asymp.Sig (2-tailed) value of 0.00 0.05 so that H0 is rejected and H1 is accepted. This shows that there is an effect of the contextual learning model assisted by E-LKPD Liveworksheets on student learning outcomes on the material of colligative properties of solutions.